The Relationship between Learning Time Management and Academic Achievement among Upper-Grade Students at SD Negeri 8 Watampone, Bone Regency - Faradilla Laura Wendari; Muh. Idris Jafar; Abd. Kadir (PT. Lontara Digitech Indonesia, 2025)
This study employed a correlational quantitative research design aimed at determining whether there is a relationship between learning time management and the academic achievement of upper-grade students at SD Negeri 8 Watampone, Bone Regency. The population of this study consisted of 72 upper-grade students at SD Negeri 8 Watampone, Bone Regency. The sample comprised students in Grades IV, V, and VI. Data on learning time management were obtained by distributing questionnaires to students, while data on students’ academic achievement were obtained from the documentation of report card scores of the students selected as the sample in this study. The data analysis techniques used were descriptive statistical analysis and inferential statistical analysis, including normality, homogeneity, and hypothesis testing. Based on the results of the descriptive statistical analysis, students’ learning time management had a mean score of 110.33, which was in the moderate category. Students’ academic achievement scores had a mean of 83.87, which was also in the moderate category. Furthermore, based on the results of the inferential statistical analysis, H₀ was rejected and H₁ was accepted. Based on the research findings, it can be concluded that there is no significant relationship between learning time management and the academic achievement of upper-grade students at SD Negeri 8 Watampone, Bone Regency.